Features of assessing the quality of meat and meat products in the market of the Republic Kazakhstan - Kaliyaskarova Е. A. (Journal of Economic Research & Business Administration, 2015)
The article describes the entry of Kazakhstan into the list of highly competitive countries, its advantages and priorities; consumer demands for meat and meat products; ways of improving the competitiveness of meat and meat products; evaluation of quality indicators of meat and meat products in Kazakhstan, lab work results; compliance with the standards; the amount of defected meat and meat products; the volume of the investigated meat and meat products comparing to the normative documents; the amount of the defected and eliminated meat and meat products by regions; the whole amount of the defected and eliminated meat and meat products in Kazakhstan; the annual dynamical changes of the market.